THE DEVELOPMENT OF SPEED AND EXPLOSIVE FORCE OF THE LOWER LIMBS IN PRIMARY SCHOOL STUDENTS THROUGH DYNAMIC GAMES - Marius Alin MARINĂU; Mirela ȘTEF; Petru PEȚAN; Adriana IGNA; Gheorghe LUCACIU (Editura Universităţii din Oradea, 2022)
Play can be considered a part of the social world of both children and adults. Taking into account the playful behavior of young school students and their enjoyment of playing, the judicious application (in terms of intensity, volume, application period) of a training program consisting of dynamic games with running content and jumping, will cause a significant increase in the manifestation indices of acceleration speed, agility and explosive strength in primary school students. The subjects of our research are 171 primary school children, of which 90 children are part of the experimental group (G.E.) and 81 of the subjects are part of the control group (G.C.). The results obtained for all the control samples used by the subjects from the two experimental groups confirm the correctness of the methods and means used. The values of the effect size (E.S.) obtained in the subjects of the experimental group (both in the case of girls and boys) confirm that the difference between the averages recorded in the two tests (T.I. and T.F.) is statistically significant.